Particulate matter atmospheric dispersion modeling and the impacts of using LNG fueled freight vehicles in São Paulo - Borges, Raquel Rocha; Teixeira, Ana Carolina Rodrigues; Mouette, Dominique; Ribeiro, Flávia Noronha Dutra (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2021)
The Brazilian transport system is based on the use of highways and heavy-duty trucks are the main vehicles used to transport goods, responsible for 70% of vehicular particulate matter (PM10) emissions in the State of São Paulo. Therefore, the search for alternative technologies to reduce emissions from the transport sector is increasing. Considering the importance of reducing pollutants emissions and the air quality improvement in large urban centers, this research aims to calculate and evaluate the particulate matter (PM10) emissions from heavy-duty trucks on an avenue (Avenida Marginal Tietê) in the city of São Paulo. For this, the atmospheric dispersion model AERMOD was used to calculate the average PM10 concentrations emitted by heavy-duty trucks powered by diesel, and the impacts derived from the replacement of 100% of this fuel by liquefied natural gas (LNG) was evaluated. Results show that the automotive technology replacement helps to reduce 99% of PM10 by the analyzed avenue, but further studies are needed to assess the total concentration and other possible impacts, such as effects on human health resulting from exposure to this pollutant on this avenue.